Evidence for nodal superconductivity in infinite-layer nickelates - Shannon P. Harvey; Bai Yang Wang; Jennifer Fowlie; Motoki Osada; Kyuho Lee; Yonghun Lee; Danfeng Li; Harold Y. Hwang (Proceedings of the National Academy of Sciences, 2025)
Infinite-layer nickelates present a new family of potential unconventional superconductors. A key open question is the superconducting pairing symmetry. We present low-temperature measurements of the magnetic penetration depth in optimally doped La 0.8 Sr 0.2 NiO 2 , Pr 0.8 Sr 0.2 NiO 2 , Nd 0.8 Sr 0.2 NiO 2 , and Nd 0.7875 Sr 0.2125 NiO 2 . For La- and Pr-nickelates, the superfluid density shows a quadratic temperature dependence, indicating nodal superconductivity in the presence of disorder. Nd-nickelate exhibits complex low-temperature behavior associated with Nd 4 f magnetism, which precludes a direct measure of the nodal structure.